Thin shells in einstein-born-infeld theory - Eiroa, E.F. (2011)
The characterization and the mechanical stability of charged thin shells with spherical symmetry are analyzed in the context of Einstein-Born-Infeld theory. The study of stability is performed by considering linearized perturbations preserving the symmetry of the static configurations. It is found that as the charge increases, the shells can be stable for a wider range of the parameters. © 2012 American Institute of Physics.